Workplace safety awareness among the production workers in wood manufacturing sector at Dongwha Malaysia (Merbok) / Muhamad Fadhil Abdul Jalall and Ahmad Shahir Mokhtar - Abdul Jalall, Muhamad Fadhil; Mokhtar, Ahmad Shahir (2018)
Safety defined as liberation from injury, risk, and danger. Safety can be a “caution” in order to avoid danger. According to the International Labour Organization, ILO (1991), safety precautions need to have a good plant design which is include the smoke detectors, sufficient emergency exit, and water sprinkler, adequate safety support on site, and regular plant maintenance, and others should always be a minimum requirement at all operational industrial site. Besides that, government also should play important role to ensure the safety at the workplace. According to Robert and Rousseau, (1989) stated that existing a safety awareness is critical and challenging for the most employer and management in organization which involve potentially harmful activities. Safety awareness can be defined as a beliefs and core assumptions that organizational members need to hold concerning safety issues (Clarke, 2003). This shown the definition of safety awareness is the sharing of common belief and values that safety is a priority.